Individual differences, autism spectrum disorder, pathological demand avoidance; impulsivity, emotional stability and delinquency - Bull, Elinor (2018)
Pathological Demand Avoidance (PDA) is a behavioural phenotype proposed by Newson in the 1980’s. PDA is characterised by an intense drive to avoid demands and expectations which can result in emotional outbursts, aggressive and impulsive behaviour. The emotional and impulsive profile of PDA indicates individuals with PDA may be vulnerable to minor offences and consequently encounter the Criminal Justice System (CJS). The current study sought to investigate the relationship between PDA, Autism Spectrum Disorder (ASD) and delinquency and whether measures of impulsivity, emotional stability, ASD and PDA predict delinquency. A significant positive relationship was found between PDA and delinquency, compared to a significant negative relationship between ASD and delinquency. Results found that measures of PDA, ASD, impulsivity and emotional stability do not significantly predict scores of delinquency. However, lower conscientiousness was found to significantly predict both delinquency and PDA, indicating specific characteristics of the PDA profile may make such individuals vulnerable to delinquency. Consequences of the findings are discussed in terms of their application to the CJS and the development of PDA becoming a separate diagnostic category.